PENGEMBANGAN MEDIA VIDEO ANIMASI PADA PEMBELAJARAN IPAS MENGGUNAKAN APLIKASI CAPCUT DI KELAS IV UPT SD NEGERI 13 SITIUNG - Muhammad Subhan; Lika Apreasta; Arwin Indah Sari (STKIP Subang, 2024)
This research aims to develop video media using the Capcut application. This research was motivated by students' difficulties in understanding science learning material and my needs, this was because the teaching materials used were still in printed/themed form. The aim of the research is to produce animated video media for science learning that is valid, effective and practical.This research uses the type of research and development or Research and Development (R&D). This research is the steps and process for developing a new product or perfecting an existing product. The author developed a new product that has not yet been used at UPT SD Negeri 13 Sitiung. The steps for developing animated videos using the Capcut application use the ADDIE development model developed by Dick and Carry in 1996. The ADDIE model is divided into four stages, namely the Analysis, Planning, Development, Implementation Stages. , and Evaluation.The results of the validation of animated video media were validated by six validators, namely graphic validation 85.41% with the very valid category, content expert validation 79.16% with the very valid category, and 89.58% validation for language experts with the very valid category. The results of the teacher response questionnaire analysis were assessed by the class IV teacher as getting an average of 90.90% in the very practical category, and the analysis of the student response questionnaire was assessed by all class IV as getting an average of 95.67% in the very practical category. The results of the effectiveness analysis were obtained from the learning outcomes of students who completed an average of 92.30% in the very effective category.